Concepções de capacidade afetam a aprendizagem motora de crianças - Drews, Ricardo (2013)
The present study investigated the effects of different ability conceptions on the learning of a throwing task in 6, 10, and 14-years-old children. In each age group, different groups were given either inherent ability (IA) or acquirable skill (AS) instructions before the beginning of practice. Participants were blindfolded and threw beanbags with their non-dominant hand at a target that was placed on the floor at a distance of 3 m. All participants performed 40 practice trials and received veridical feedback (accuracy score) after each trial. One day after the practice phase, retention and transfer (4 m) tests (10 trials each) without instruction or feedback about conceptions of ability, each consisting of 10 trials. As expected, older participants had higher accuracy scores in both practice and retention/transfer than younger participants. Importantly, instructions highlighting the malleability of the skill (AS groups) provided on Day 1 resulted in greater throwing accuracy in retention and transfer than did those implying an underlying inherent ability (IA groups). Thus, the induced conceptions of ability influenced the learning of the throwing task regardless of the children s age. Previous findings (Wulf & Lewthwaite, 2009) suggest that AS conceptions of ability facilitate automaticy in movement control, presumably by reducing learners concerns about their performance and ability. The present findings add to the increasing evidence of motivational influences on motor skill learning and demonstrate that these effects generalize to children. The findings underscore the importance of how instructions are worded in the context of teaching and learning